Internal control, corruption and money laundering - IONESCU, Luminiţa; POWER, Mary (Annals of Spiru Haret University. Economic Series, 2011)
The global financial crises created a different context for the economic growth and globalization. In the last few years, five risks have been designated as “risks to watch”, as survey respondents assessed them with high levels of variance and low levels of confidence while experts[1] consider they may have severe, unexpected or underappreciated consequences: cyber-security, demographic challenges, resource security, retrenchment from globalization, weapons of mass destruction. Strongly connected to these risks others are important to analyze: corruption, illegal trade and money laundering. There is a strong relation between corruption and money laundering. During the economic crunch the level of corruption and fraud had scientifically increased. Internal control could be a good instrument to reduce corruption and to stop the illegal trade and money laundering. Internal control is a dynamic integral process that is continuously adapting to the changes an organization is facing [1] www.weforum.org – The Global Risks Report 2010-2011.